SKAML: An XML Markup Language for Abstract Skeleton Definitions in the Context of Human Posture Assessments - Lins, Christian; Fudickar, Sebastian; Hein, Andreas (Medical Informatics Europe, 2018)
An XML-dialect for the description and configuration of abstract human skeletons for ergonomics assessments with motion capture (MoCap) systems -the Skeletal Assessment Markup Language (SKAML) -is presented. A SKAML document is the semantic description of the MoCap system and assessment method conjunction. It describes the skeletal system of a human body as a system of rigid bones and joints from a MoCap observer perspective and allows straightforward combinations of MoCap data and digitized methods for ergonomics assessments. We anticipate our work as help for researchers and developers that implement new assessment methods or MoCap systems.
Keywords: Ergonomics Assessment; Informationenfehlen; Motion capture; Musculoskeletal Disorders; Skeleton Markup; UNIAMT; UNILLM; Unpublished